Regulação do tratamento de dados pessoais e contribuições ao combate do abuso do poder econômico - Bueno, Samara Schuch (2019)
In this Dissertation, we will study how the progress of computational technology, internet, and the monetization of data are challenging legal and economic experts to understand the characteristics and the dynamic of our society based on personal information, aiming to develop methods to mitigate abuses, mainly the economic ones. Through the analysis of real cases of economic abuse examined by the competition and data protection authorities, it will be clear that the abuse of processing data may cause heavy damages, to owners of data, as individuals or consumers. Thus, we also will study how personal data result in economic power in the actual market and how the asymmetry of power allows market domination practices. Finally, we will see how CADE (The Brazilian Administrative Council for Economic Defense) and the recentlyenacted Law 13.709/2018 (Brazilian General Data Protection Act) contributes to the fight against economic abuses, mainly market domination practices based on the processing of personal data.